Selected philosophical concepts and medical activities for the improvement of the quality of life and development - Letkiewicz, Sławomir (Studia Ecologiae et Bioethicae, 2010)
Constitutional features of ethics in general, in both the descriptive and normative meanings, or deontology, are certainly freedom of choice strictly related to responsibility, the axiological system, etc. I advance a thesis that ethical eidetic must concentrate on the issue of human honesty. The analyzed ethical proposals, those of Friedrich Nietzsche and Józef Bańka, place the importance of philosophical reflection and speculation on this issue. The modern axiological crisis is a result of the collapse of authorities and not, inversely, that the destruction came from relativism and post-modernistic anarchism. It is easy to be disinterestedly honest; it is more difficult when its rules are being “observed” by a “daimonion”, which is transcendental to a human. Perhaps it is time for authentic, disinterested honesty, both in the rules of ethics and in deontology, and also, or perhaps mainly, in medical ethics, which has essential significance for the improvement of life quality, constituting an essential criterion in the process of realizing development. But if the honesty does, during the building of the technical civilization?